2013
DOI: 10.1185/03007995.2013.802230
|View full text |Cite
|
Sign up to set email alerts
|

Real-life effectiveness and tolerability of the rivastigmine transdermal patch in patients with mild-to-moderate Alzheimer’s disease: the EMBRACE study

Abstract: The rivastigmine transdermal patch is effective in maintaining cognitive function over 18 months of treatment in patients with mild-to-moderate AD. The safety profile was comparable to the data in the Canadian product monograph. Lack of a comparator group is a potential limitation of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
1
10
1
Order By: Relevance
“…The results of the current study showed higher caregivers’ preference (82.4%) to rivastigmine transdermal patch for patients exposed to both forms of medication, and the findings were consistent with previous studies. 12 , 19 The current study, however, did not show a clear preference of caregivers for either oral or transdermal treatment, which was due to the prior exposure to particular form of therapy influencing the caregivers’ preference.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The results of the current study showed higher caregivers’ preference (82.4%) to rivastigmine transdermal patch for patients exposed to both forms of medication, and the findings were consistent with previous studies. 12 , 19 The current study, however, did not show a clear preference of caregivers for either oral or transdermal treatment, which was due to the prior exposure to particular form of therapy influencing the caregivers’ preference.…”
Section: Discussioncontrasting
confidence: 79%
“…Previously, the IDEAL, 12 Alzheimer disease: eXamination of patiEnt comPliance and caregiver satisfacTion (AXEPT), 20 Effective Management of Alzheimer’s Disease By TReating pAtients and relieving Caregivers with Exelon Patch (EMBRACE), 19 ENTERPRISE, 21 global RECAP study, 13 and an observational clinical study 22 have assessed the caregiver preference and/or satisfaction for the treatment of AD. IDEAL was the first pivotal trial 17 , 23 to demonstrate the non-inferiority of the rivastigmine transdermal patch over oral capsules; the study 12 also showed higher caregivers’ preference (72%) for the rivastigmine transdermal patch compared with oral capsules.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Similarly, the EMBRACE (Effective Management of Alzheimer’s disease By tReating pAtients and relieving Caregivers with Exelon patch) study, which assessed the real-life effectiveness and tolerability of rivastigmine patch, showed high caregivers’ preference (88.2%) for the patch over oral medication in patients with mild-to-moderate AD. 15 Moreover, results from a recent observational study in patients with mild-to-moderate AD have reported that the transdermal formulation of rivastigmine reduces caregiver burden in daily practice. 31 Compared with these studies, the RECAP study was unique in geographical scope and was conducted in countries where patients with AD are reported to live predominantly in households with extended families.…”
Section: Discussionmentioning
confidence: 99%
“…98 As with other cholinesterase inhibitors, it can be safely co-administered with memantine, an N-methyl-Daspartate antagonist. 99 The efficacy of the rivastigmine transdermal system is established in multiple randomized, double-blind, placebo-controlled clinical trials in persons with Alzheimer's disease 100,101,102,103 and one controlled trial of the oral formulation of rivastigmine in persons with dementia associated with Parkinson disease. 104 In controlled trials the adverse effects most commonly reported were nausea, vomiting, and diarrhea, which were dose-related and also more frequently reported in patients receiving the capsule formulation.…”
Section: Rivastigmine (Exelon)mentioning
confidence: 99%